Material Resignification in the Amazon. A way to construct sustainability scenarios - Sarmento, Fernanda [UNESP]; Moura, Monica [UNESP] (Routledge Journals, Taylor & Francis Ltd, 2017)
This article analyzes local development processes in forest areas in the Amazon. It presents the emergence of a number of nuclei that represent social innovation processes, motivated by the introduction of craft technologies for rubber vulcanization. Based mainly on the Design for Social Innovation and Sustainability approach (MANZINI, 2008), initiatives, as well as some challenges observed in the field, were examined to ensure that sustainable actions could result from these processes. Possible interactions with designers aligned in this context, and processes that enable valorization of biological, social and cultural diversity were also considered.
Keywords: Design for sustainability; Amazon local development; rubber innovation; and forest conservation